2017
DOI: 10.1039/c7ra04704e
|View full text |Cite
|
Sign up to set email alerts
|

Evidencing the diversity and needs of adjustment of the nutritional requirements for hydrocarbon-degrading activity of Pseudomonas aeruginosa adapted to harsh conditions using 2nfull factorial design

Abstract: Nutritional requirements of the most widely used bacterium,P. aeruginosa, was shown to be necessary to predict in advance to prevent failure of oil hydrocarbon bioremediation due to weathering processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…They were previously isolated from the same soil used for the extraction of hydrocarbons in this study and identified by ribotyping [ 1 , 13 ]. Cultures were performed in MSM medium as previously optimized and published by Attar et al [ 10 ]. The initial pH was 7.2, as that of the used soils.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were previously isolated from the same soil used for the extraction of hydrocarbons in this study and identified by ribotyping [ 1 , 13 ]. Cultures were performed in MSM medium as previously optimized and published by Attar et al [ 10 ]. The initial pH was 7.2, as that of the used soils.…”
Section: Methodsmentioning
confidence: 99%
“…The initial pH was 7.2, as that of the used soils. The C/N/P was adjusted to 100/10/1 using ammonium nitrate as a nitrogen source, and a mixture of KH 2 PO 4 /Na 2 HPO 4 and as phosphorus source Attar et al [ 10 ]. All the experiments were performed in a shaker set at 37 °C and 200 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…A 2 mL aliquot of the liquid was then added to 20 mL of mineral salt medium (MSM) supplemented with 1 mL of diesel or crude oil as a carbon source. This adaptation step was repeated three times to ensure that the medium was enriched with bacteria capable of growing using hydrocarbons in crude oil or diesel [ 19 , 21 , 22 ]. A 100 μL aliquot of an enriched LB liquid culture was then spread on MSM agar, then 100 μL of crude oil or diesel was sprayed onto the agar.…”
Section: Methodsmentioning
confidence: 99%
“…Only microorganisms with structures and functions well-adapted to the conditions can grow in harsh environments like the environment in Qatar. Such microorganisms are interesting because they have particular abilities to degrade or transform unconventional mixtures of organic compounds, as was found in studies performed by Al Disi et al [ 19 ] and Attar et al [ 21 ]. Natural microbial remediation in Qatar is therefore an appropriate model for the degradation of weathered hydrocarbons in harsh soils.…”
Section: Introductionmentioning
confidence: 99%